Pseudomonas aeruginosa Pneumonia: Evolution of Antimicrobial Resistance and Implications for Therapy - Lynch, Joseph P., III; Zhanel, George G. (Seminars in Respiratory and Critical Care Medicine, 2022)
Pseudomonas aeruginosa (PA), a non–lactose-fermenting gram-negative bacillus, is a common cause of nosocomial infections in critically ill or debilitated patients, particularly ventilator-associated pneumonia (VAP), and infections of urinary tract, intra-abdominal, wounds, skin/soft tissue, and bloodstream. PA rarely affects healthy individuals, but may cause serious infections in patients with chronic structural lung disease, comorbidities, advanced age, impaired immune defenses, or with medical devices (e.g., urinary or intravascular catheters, foreign bodies). Treatment of pseudomonal infections is difficult, as PA is intrinsically resistant to multiple antimicrobials, and may acquire new resistance determinants even while on antimicrobial therapy. Mortality associated with pseudomonal VAP or bacteremias is high (> 35%) and optimal therapy is controversial. Over the past three decades, antimicrobial resistance (AMR) among PA has escalated globally, via dissemination of several international multidrug resistant “epidemic” clones. We discuss the importance of PA as a cause of pneumonia including health care–associated pneumonia, hospital-acquired pneumonia, VAP, the emergence of AMR to this pathogen, and approaches to therapy (both empirical and definitive).
Keywords: multidrug resistance; antimicrobial resistance; Pseudomonas aeruginosa; plasmids; clonal spread; carbapenemases; ventilator-associated pneumonia